PROSES PEMERIKSAAN GUGATAN PERDATA DI PENGADILAN NEGERI - Maria Rosalina; Danialsyah Danialsyah; Yosi Chairunnazmi Ritonga; M. Daffa Naufal; M. Yusuf Syafwan S (Universitas Islam Sumatear Utara, 2023)
The court is an institution where the community seeks justice, by filing a lawsuit. Lawsuit is a claim for rights filed by the plaintiff against the defendant through the court, because the plaintiff feels his rights have been harmed by the defendant. There are at least 2 (two) or more parties defending their rights in the lawsuit civil procedural law, namely the plaintiff and the defendant. In filing a lawsuit there are 2 (two) types of lawsuits, namely voluntary and contentious. Voluntary lawsuits or so-called requests are made on the basis of the interests of only one party without any element of dispute. Contributory lawsuit is a lawsuit for a problem submitted where the parties are at least 2 (two) people and have an element of dispute . In everyday life in the community, there are many legal problems, especially in the civil field that can be filed for lawsuits or requests to court. However, the community does not yet know and understand how the process of examining civil lawsuits in district courts, as well as community members who live in villages Baja Kuning, Tanjung Pura District, Langkat Regency. Some civil issues that occurred in Baja Kuning Village such as divorce, determination of heirs, assets gono like this, land disputes, household issues and others. The people in Baja Kuning Village wish to take legal action in courts in solving their problems, but they do not understand how the process is. Based on this fact, it encourages extension officers to carry out Legal Counseling with the Community Service model entitled The Civil Lawsuit Examination Process in the District Court.